Phytosanitary situation of maize streak virus in the main maize production zones of Cameroon - Mbong, G.A.; Suh, C.; Sime, H.D.; Anoumaa, M.; Fonkou, T.; Nkombo, L.L.C.; Meseka, S.K.; Kumar, P. Lava; Menkir, A. (Scientific Research Publishing, Inc., 2021)
Maize streak caused by the Maize streak virus (MSV, genus Mastrevirus) is transmitted by Cicadulina spp., and is responsible for considerable maize yield losses in all maize production zones in Africa, including Cameroon. A survey was conducted in 3 agro-ecological zones (AEZ) of Cameroon (Sudano-Sahelian: zone I, Western Highlands: zone III and Bimodal Rainforest: zone V) between November 2017 and November 2019 to determine the status of streak disease in maize farms. The incidence and severity were determined in 90 maize fields, 30 fields per AEZ; the effect of lightning on the disease was also assessed using 15 fields under shade and 15 opened fields per AEZ. The highest streak disease incidence (60%) was found in AEZ I, whereas the lowest incidence was 10% in AEZV. The highest disease incidence and severity (80% and 4.5 respectively) were observed in maize fields under shade as compared to open fields (70% and 4.5 respectively). The phylogenetic analysis of MSV sequences from symptomatic plants indicated it as MSV-A strain identical to be previously reported to determine the virus diversity in relation to the other characterization isolates. This information is important for the development of control strategies to limit yield losses due to MSV.